Relay [videorecording (DVD)] - Piasecki, Justin; Ahmed, Riz, 1982-; James, Lily, 1989-; Worthington, Sam, 1976-; Fitzgerald, Willa; Davis, Eisa; Maher, Matthew (Actor); Garber, Victor; Nuttgens, Giles; Morshead Alana; Doogan, Tony (Bleecker Street, 2025)
"Relay follows a world class 'fixer' who brokers lucrative payoffs between corrupt corporations and the individuals who threaten their ruin. He keeps his identity a secret through meticulous planning and always follows an exacting set of rules. When a new message arrives from a potential client needing his protection to stay alive, the rules quickly start to change"--